CT-GUIDED FNAC AND BIOPSY : OUR EXPERIENCE - SREE RAM, MN (Med J Armed Forces India, 1995)
Twenty five patients with mass lesions in the chest, abdomen, pelvis, and paraspinal region underwent contrast enhanced computed tomographic scan (CT Scan) followed by CT guided FNAC or Tru-cut biopsy. CT was found to be extremely valuable in ensuring needle placement within the lesion. It also helped in avoiding the necrotic areas and obtaining tissue from an area most likely to yield an adequate sample. A post-procedure scan helped in ruling out post-procedure complications.